The concept of "spectrum" in Jacques Derrida's philosophy of exclusion and evocation (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This research is an interpretive and critical approach to one of Jacques Derrida's theories of deconstructive philosophy, the term "spectrum", which focuses first on trying to define and clarify the meanings that can be contained within Derrida's texts, and then sheds light on its location and importance for the School of Methodological Practice , And in a third stage, this paper presents an illustration of Derrida's divergence regarding the concept of the spectrum that this argument indicates between exclusion and retention and how Derrida's position can be interpreted in this regard. Finally, this research presents a critical approach to the functional role of Derrida's philosophy .